Potensi Ochrobactrum intermedium - C939A31, Klebsiella oxytoca - C939A32, Bacillus subtilis- I308A32 Asal Tanaman Kopi untuk Mengendalikan Nematoda Luka Akar Pratylenchus coffeae - Dwi Halimah; Abdul Munif; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2016)
Infection of root lession nematode, Pratylenchus coffeae, becomes an important factor causing yield loss in coffee production in Indonesia. Biological control of P. coffeae needs to be developed to meet the requirement of environmentally save crop production.  The research was conducted to evaluate 3 selected endophytic bacteria isolates, Ochrobactrum intermedium DSQ5, Klebsiella oxytoca NGB-FR 50, and Bacillus  subtilis AIMST 10.T18.1, from coffee in controlling P. coffeae. Research methods involved pathogenicity test based on hypersensitive reaction and haemolysis test, and evaluation of their ability to suppress P. coffeae in vitro and in planta. The hypersensitive and haemolysis reactions indicated that these 3 isolates showed negative result both to plant and human. In vitro assays showed that two isolates, K. oxytoca - C939A32 and O. intermedium - C939A3, could suppress P. coffeae populations by 66.7% and 100%. Those results correlated positively with in planta assay’s result.